Analytic structure of weighted shifts on directed trees. Issue 11 (8th December 2016) - Budzyński, P.; Dymek, P.; Ptak, M.
Abstract : We show that a weighted shift on a directed tree is related to a multiplier algebra of coefficients of analytic functions. We use this relation to study spectral properties of the operator in question.